Needleless Electrospinning and Electrospraying of Mixture of Polymer and Aerogel Particles on Textile. (23rd May 2018) - Shaid, Abu; Wang, Lijing; Padhye, Rajiv; Jadhav, Amit
Abstract : Needleless electrospinning and electrospraying of aerogel particles in comparatively lower electric voltage (9 kV) have been demonstrated in the paper. Aerogel particles were dispersed in polymer solution and then needlelessly electrospun/sprayed by creating high electric charge at the syringe tip using a curved wire. FTIR spectra and SEM images proved that aerogel particles were deposited onto the base textile. In case of electrospinning, a nanofibre web holding the aerogel particles covered the fabric surface, whereas in case of electrospraying, aerogel particles deposited with the microdroplets of the polymer. The electrospraying process showed great potential for fabric surface functionalization due to the high amount of particle deposition on fabric. The new approach can be applicable for transferring other particulate materials on fabric surface through needleless electrospinning and electrospraying processes.